Distribution of Coral Cover and Benthic Substrate Composition in the GITA NADA Marine Protected Area, West Lombok - Raja Aditya Sahala Siagian; Relis Gabriel Sihaloho; Muhammad Farhan Anshory; Ivonne Herlina Tani; Muhamad Dipa Hariadi; Kara M A Majerus (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro, 2026)
Coral reefs in Indonesia are under increasing pressure from natural and anthropogenic disturbances, requiring detailed spatial assessments to support effective management. This study assessed coral cover condition and benthic substrate composition across management zones of the Gili Tangkong-Gili Nanggu-Gili Sudak (GITA NADA) Marine Protected Area (MPA), West Lombok, Indonesia. We conducted surveys from October 2023 to August 2024 across 46 stations using the Underwater Photo Transect (UPT) method. Sampling occurred in two depth categories: 44 shallow surveys at 3-5 m and 39 deep surveys at 8-10 m, as not all stations included both depth zones. We analyzed benthic photographs using CPCe software to quantify coral cover and substrate categories. Mean coral cover at 3-5 m depth was 32.57% ± 20.57%, classified as fair, whereas coral cover at 8-10 m depth averaged 17.51% ± 11.90%, indicating poor reef condition. Kruskal-Wallis analysis showed a significant difference in coral cover between depths (P < 0.05), with shallow reefs supporting higher coral cover than deeper reefs. At shallow depths, coral cover in the Fisheries, Utilization, and Other-use Zones was generally fair, while the Core Zone was classified as poor. In contrast, coral cover at 8-10 m depth was predominantly poor across all zones. Kruskal-Wallis analysis showed no significant difference in coral cover among management zones at either depth (P > 0.05). Substrate composition at 3-5 m depth was dominated by hard coral and rubble, whereas deeper reefs were characterized by high proportions of rubble and silt, reflecting habitat degradation and limited reef resilience. This study represents one of the first comprehensive UPT-based assessments of coral cover and benthic substrate composition across management zones within the GITA NADA MPA. These results indicate widespread coral reef degradation in the GITA NADA MPA, particularly at deeper depths, highlighting the need to re-evaluate zoning effectiveness, strengthen enforcement, and implement targeted reef restoration and sediment management strategies.